Zastosowanie metody perturbacji do analizy plastycznego płynięcia ośrodka typu Coulomba w stanie osiowej symetrii - Ryszard IZBICKI (Engineering Transactions, 1970)
Application of the perturbation method to the analysis of the plastic flow of a Coulomb type body in an axially symmetric state